Sphenofrontal distance in euploid and aneuploid fetuses. (9th July 2017) - Abele, H.; Sonek, J.; Goldschmid, D.; Wagner, P.; Hoopmann, M.; Kagan, K. O.
ABSTRACT: Objective: To examine the sphenofrontal distance (SFD) in a large series of aneuploid fetuses in the second and third trimesters and compare findings with those of a euploid population. Methods: The database at our unit was searched to identify pregnancies with a diagnosis of trisomy 21, 18 or 13, triploidy or Turner syndrome after 15 weeks' gestation. Stored ultrasound images obtained between 19 and 22 weeks were reviewed. For the normal population, two euploid fetuses matched for gestational age were selected randomly for each aneuploid case. The SFD was measured from the anterior edge of the sphenoid bone to the lowest posterior edge of the frontal bone using on‐screen calipers. The SFD measurement was parallel to the long axis of the maxilla. If the sphenoid bone did not extend superiorly enough for direct measurement of the SFD, a tangential line was drawn at the anterior wall of the sphenoid bone and extended cranially. In these cases, the distance between the extended line and the frontal bone was measured. One operator measured the SFD twice and was blinded to the results and karyotype. Results: The study population consisted of 591 pregnancies: 394 euploid fetuses, 122 fetuses with trisomy 21, 45 with trisomy 18, 16 with trisomy 13, eight with Turner syndrome and six with triploidy. For both euploid and aneuploid groups, mean gestational age at examination was 22.8 (range: euploid, 15.0–40.7; aneuploid, 15.0–40.3) weeks. For euploid fetuses, mean SFD was 1.27 cm and measurements ranged from 0.53 cm to 2.56 cm. SFD was significantly dependent on gestational age (SFD = 0.138 + 0.005 × gestational age, P < 0.001, r = 0.802). Mean SFD was significantly smaller in each aneuploid group compared with the euploid population (trisomies 21, 18 and 13: all P < 0.001; triploidy: P = 0.026; Turner syndrome: P = 0.047). For 32 (26.2%), nine (20.0%) and six (37.5%) fetuses with trisomy 21, 18 and 13, respectively, SFD was < 5 th percentile. Only one (12.5%) fetus with Turner syndrome and none with triploidy had SFD < 5 th percentile. Conclusion: In aneuploid fetuses, the SFD is smaller than in their euploid counterparts. However, for a false‐positive rate of 5%, the detection rate of trisomy 21 is only 26%. Therefore, using the method we have proposed, it is unlikely that this marker will play a major role in second‐ and third‐trimester screening for aneuploidy. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.